FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN ANEMIA PADA REMAJA PUTRI DI SMP N 3 KECAMATAN TEBING KABUPATEN KARIMUN TAHUN 2017 - Kurniawati Ningsih; Saiful Batubara (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2017)
Anemia is one of nutrition problen in the world. The incidences of anemia in Indonesia are relatively high. The prevalence of anemia at Karimun Regency happened on 729 schoolgirls (12.8%) in 2016. Pre-survey done on 20 school girls from SMP N 3 Tebing showed that 6 girls (30%) got anemia. This study was to invertigate the factors concerning anemia incidences on school girls at SMP N 3Tebing of Karimun Regency. The study used cross sectional approach with 62 girls as samples after systematic sampling technique. Data collection was done through questionnaires and Hb test. The correlation analysis was done by using chi square. Result found that38 students got anemia (61.3%). Statistical test showed that factors concerning anemia are knowledge leve3l (p=0.011), meal schedule (p=0.021) and menstrual pattern (p=0.022). Thw\e school health unit should intensity anemia prevention program on school girls by giving socialization about anemia and distributing Fe tablet..Â